2021
DOI: 10.3389/fmicb.2021.643025
|View full text |Cite
|
Sign up to set email alerts
|

Specific Microbial Taxa and Functional Capacity Contribute to Chicken Abdominal Fat Deposition

Abstract: Genetically selected chickens with better growth and early maturation show an incidental increase in abdominal fat deposition (AFD). Accumulating evidence reveals a strong association between gut microbiota and adiposity. However, studies focusing on the role of gut microbiota in chicken obesity in conventional breeds are limited. Therefore, 400 random broilers with different levels of AFD were used to investigate the gut microbial taxa related to AFD by 16S rRNA gene sequencing of 76 representative samples, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 59 publications
(74 reference statements)
5
38
1
Order By: Relevance
“…Clarifying the mechanisms of lipogenesis is essential for the improvement of the fat trait in chicken. Studies have revealed that gut microbiota participates in the regulation of lipogenesis and fat deposition in chicken [ 7 , 10 ]. However, the precise molecular mechanisms by which gut microbiota regulates lipogenesis and fat deposition remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Clarifying the mechanisms of lipogenesis is essential for the improvement of the fat trait in chicken. Studies have revealed that gut microbiota participates in the regulation of lipogenesis and fat deposition in chicken [ 7 , 10 ]. However, the precise molecular mechanisms by which gut microbiota regulates lipogenesis and fat deposition remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, R. bacterium CPB6 mainly produces caproate, which had positive relations with BMI ( Zhu et al, 2017 ; Fan et al, 2018 ). Similarly, R. bacterium has also been identified to significantly increase in cecum of high AFD chicken ( Xiang et al, 2021 ). Increased abundances of Alistipes sp.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to microbial relative abundance, genera including Megamonas ( Maya-Lucas et al, 2019 ), Oscillospira , Ruminococcus ( Jiao et al, 2018 ), Fusobacterium , Escherichia-Shigella , and Pseudomonas ( Gao et al, 2018 ) were significantly increased in obese humans and mice. Recently, studies on chicken cecal microbiome showed that Microbacterium , Sphingonomas , Olsenella , Methanobrevibacter , and Slackia were positively correlated with fat metabolism ( Xiang et al, 2021 ; Zhang et al, 2021 ). Functional analysis of microbiome indicated that pyruvate metabolism, butanoate metabolism, propanoate metabolism, pentose phosphate pathway, fatty acid biosynthesis, and glycerolipid metabolism pathways were enriched in obese mice ( Jiao et al, 2018 ), while glycolysis I (from glucose 6-phosphate) and glycolysis II (from fructose 6-phosphate) were significantly overrepresented in normal individuals ( Maya-Lucas et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance of Firmicutes and Bacteroidetes is measured as a ratio, Firmicutes / Bacteroidetes (F/B), which is a predictive marker reflecting gut microbiota dysbiosis ( 72 , 73 ). Besides, the increment of the F/B ratio induced by the contraction of Bacteroidetes and/or expansion of Firmicutes is tightly associated with fat accumulation and potential for obesity both in humans and other animals ( 74 , 75 ). Recently, several reports have suggested that the gut microbiota of stressed birds presented a significantly increased trend of the F/B ratio ( 76 78 ).…”
Section: Discussionmentioning
confidence: 99%